Aspek Kohesi Gramatikal dan Leksikal pada Berita Berbahasa Jawa dalam Tabloid Jawacana - Eko Sri Cahyono; Budi Waluyo; Rahmat Rahmat (Universitas Sebelas Maret, 2022)
Abstract This research is motivated by the discrepancy between words, phrases, clauses and sentences in a discourse. Aspects of grammatical and lexical cohesion is one of the important aspects in the formation of standard discourse, especially in news discourse. Thus, it can be formulated in this study, how is the use of grammatical and lexical cohesion aspects in Javanese news? This study uses the object of analysis in the form of news in Javanese language with a culinary theme contained in the Jawacana tabloid. This study aims to describe the use of grammatical and lexical cohesion aspects in Javanese news in the Jawacana tabloid. This study uses a qualitative descriptive approach. The data collection technique is done by document analysis. The data in this study are written data in the form of words, phrases, clauses and sentences that contain grammatical and lexical cohesion aspects in Javanese news stories contained in the Jawacana tabloid. Test the validity of the data obtained through data triangulation and theory triangulation. The results of the study indicate that news in Jawacana has used grammatical and lexical cohesion in the preparation of its discourse. Thus, the discourse in thetabloid Jawacana has met the criteria as a complete and standard discourse.